Long-term stimulation with alternating electric fields modulates the differentiation and mineralization of human pre-osteoblasts - Sahm, Franziska; Freiin Grote, Vivica; Zimmermann, Julius; Haack, Fiete; Uhrmacher, Adelinde M.; van Rienen, Ursula; Bader, Rainer; Detsch, Rainer; Jonitz-Heincke, Anika (Frontiers in Physiology, 2022)
Biophysical stimulation by electric fields can promote bone formation in bone defects of critical size. Even though, long-term effects of alternating electric fields on the differentiation of osteoblasts are not fully understood. Human pre-osteoblasts were stimulated over 31 days to gain more information about these cellular processes. An alternating electric field with 0.7 Vrms and 20 Hz at two distances was applied and viability, mineralization, gene expression, and protein release of differentiation factors were analyzed. The viability was enhanced during the first days of stimulation. A higher electric field resulted in upregulation of typical osteogenic markers like osteoprotegerin, osteopontin, and interleukin 6, but no significant changes in mineralization. Upregulation of the osteogenic markers could be detected with a lower electric field after the first days of stimulation. As a significant increase in the mineralized matrix was identified, positive osteogenic effects of low alternating electric fields can be assumed.